Molecular Docking and Molecular Dynamic Studies of Secondary Metabolites from Momordica Charantia as Natural Antidiabetic: Studi Penambatan dan Dinamika Molekuler Senyawa Metabolit Sekunder Momordica Charantia sebagai Antidiabetes Alami - Rollando, Rollando; Chandra, Melisa Dwi; Aftoni, Muhammad Hilmi; Swastika, Windra (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2024)
Background: Diabetes Mellitus is a non-contagious disease characterized by hyperglycemia. Diabetes mellitus occurs when the body cannot receive or use insulin properly. If you already have diabetes, then the patient must take medication continuously because diabetes mellitus is a lifelong disease. Because medicines are quite expensive, alternative ways to cure the disease are needed by consuming traditional medicines, one of which is bitter melon (Momordica charantia). Objectives: This research aims to predict the secondary metabolite compounds in the bitter melon plant, analyze molecular interactions, and identify compounds that can lower blood sugar levels. Material and Methods: 12 compounds from the Momordica charantia plant and six proteins (1IR3, 1RHF, 1XU7, 4PNZ, 4YVP, 2NT7) that will be docked using Pyrx and Yasara Dynamics applications. Results: From the molecular docking results, three compounds with the highest binding affinity were found in Momordica charantia: momordenol, oleanolic acid, and momordicin. Based on molecular dynamics simulations, these three compounds were stable in their interactions with the six proteins tested, namely 1IR3, 1RHF, 4PNZ, 4YVP, 1XU7, and 2NT7. Momordenol and momordicin showed the most stable interaction profiles. Furthermore, ADMET tests showed that momordenol, oleanolic acid, and momordisin have drug-like characteristics. Conclusions: The Momordica charantia plant has the potential to act as an antidiabetic agent.